Portraying entanglement between molecular qubits with four-dimensional inelastic neutron scattering - E. Garlatti (Nature Portfolio, 2017)
Showing the presence of quantum entanglement in a system means it is beyond a classical description, but this is difficult to do experimentally. Here, the authors show how four-dimensional inelastic neutron scattering can quantify entanglement, demonstrating the method on a supramolecular dimer.